Rethinking corporate social responsibility in the age of climate change: a communication perspective - Myria Allen; Christopher A. Craig (International Journal of Corporate Social Responsibility (JCSR), 2016)
In the winter of 2015 world leaders presented plans for keeping the global temperature rise below 2 êC due to projected climate change threats. These threats present organizations, communities, and citizens with the need to change viewing corporate social responsibility (CSR) as a voluntary luxury to being a necessity. This essay proposes refocusing CSR efforts in light of projected climate challenges and expanding our investigation into the role of communication in such efforts. Communication is more than a tool to craft a positive corporate image so as to gain or protect legitimacy. It is the means through which CSR sustainability-related initiatives are created and disseminated within organizations and among their key stakeholders (i.e., governments, communities, competitors, supply chains, employees). Suggestions for future research exploring CSR, sustainability, and communication are offered.
Keywords: 650; Climate change; Corporate social responsibility; Sustainability; Corporate communication